Kinetic energy redistribution on the hydrodynamic initial section - Носко, Сергей Викторович; Шевчук, Александр Анатолиевич (Technology audit and production reserves, 2014)
Scientific and technical information, regarding the issues of viscous and abnormally viscous liquid flow in geometrically heterogeneous channels is analyzed. The reasons of additional energy losses, caused by the occurrence of the inertial forces in the flow during the development of the velocity profile on the hydrodynamic initial section of channels are determined. Kinematic characteristics of unstabilized flow under various conditions of entry in the initial section are investigated. The analysis of kinetic energy redistribution in the flow is carried out. The functional dependence of the Coriolis coefficient on hydrodynamic conditions of entry in the initial section is found, and formulas to calculate its length are defined. An opportunity to identify additional pressure losses without using the hydrodynamic section method, associated with restructuring the velocity profile on its length is provided. Calculated dependences to compute the length of the flow stabilization section are defined. The obtained results of «control» over the hydrodynamic conditions of entry allow to create the optimal operating modes and improve performance characteristics of the process equipment.